Inter-arm blood pressure difference in healthy young adults: a cross-sectional study - Pun, Dilli Bahadur; Chaudhary, Sonam; Shrestha, Prashanna; Thapa, Bobby; Madhikarmi, Nirjala Laxmi (Journal of Physiological Society of Nepal, 2020)
Introduction: Inter-arm difference (IAD) in blood pressure is the difference in the systolic and the diastolic blood pressure between arms of an individual. Studies regarding IAD among elderly, pregnant women, patients with cardiovascular disease and diabetes have been conducted but there are very limited studies carried out among young healthy adults. Thus, this study aimed to investigate the inter-arm blood pressure difference and its association with age, sex, BMI and family history of hypertension among Nepalese healthy young adults.Materials and methods: A cross-sectional study was carried out among 230 students of Kantipur Dental College, Kathmandu, Nepal. Blood pressure was measured using a mercurial sphygmomanometer. Statistical analysis was done using paired t test, chi-square and Pearson’s correlation test using SPSS 16.Results: The absolute mean IAD for SBP was 5.03±3.88 mm Hg and for DBP was 3.84±3.77 mm Hg. There is significant inter-arm difference for SBP (t=4.882, p